QUISTE GLANDULAR ODONTOGÉNICO (2018)
This is a case report of a glandular odontogenic cyst in an uncommon localization. A brief review of the clinical and diagnostic aspects of a GOC is also presented. The glandular odontogenic cyst (GOC) is a rare jawbone cyst of odontogenic origin with unique histopathologic features and an unclear histogenesis.